2020
DOI: 10.3855/jidc.11973
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Campylobacter spp. in Brazilian poultry processing plants

Abstract: Introduction: Campylobacteriosis is considered the most common bacteria-caused human gastroenteritis in the world. Poultry is a major reservoir of Campylobacter. Human infection may occur by consumption of raw and undercooked poultry or by contamination of other foods by these items. The aim of this study was to assess the prevalence of Campylobacter spp. in poultry processing plants with conventional culture method and real-time PCR. Methodology: A total of 108 poultry processing plant samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…However, unlike the European Union and United States, there is no specific legislation in the country for the analysis of Campylobacter. Moreover, campylobacteriosis is still underreported, and epidemiological and molecular studies on the diversity and virulence of C. jejuni are still few in the country 29,53 . Our results reinforce the urgent need for specific legislation adoption to prevent the spread of potentially pathogenic strains through the consumption of poultry products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike the European Union and United States, there is no specific legislation in the country for the analysis of Campylobacter. Moreover, campylobacteriosis is still underreported, and epidemiological and molecular studies on the diversity and virulence of C. jejuni are still few in the country 29,53 . Our results reinforce the urgent need for specific legislation adoption to prevent the spread of potentially pathogenic strains through the consumption of poultry products.…”
Section: Discussionmentioning
confidence: 99%
“…The processing line was operated under standard commercial conditions. In total, 980 samples were collected from swabs (cloacal and transportation boxes), water from the chiller tank, and carcasses throughout the slaughter line, as previously described by Borges et al 53 . The samples were stored in isothermal ice boxes and taken to the laboratory for identification.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the prevalence of C. jejuni and C. coli was 94.5% and 5.5%, respectively (Sánchez et al, 2017). In one study, the detection of Campylobacter on carcasses was higher than that on cloacal swabs, which could indicate cross-contamination during the slaughtering process (Borges et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, cleaning and disinfection procedures are crucial to avoid cross-contamination among flocks. Previous studies have shown that Campylobacter contamination was retained or substantially increased when the cleaning and disinfection procedures were ineffective ( Peyrat et al, 2008 ; Borges et al, 2020 ; Perdoncini et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%